Some insights into Stirling machine behaviour - Tucker, AS; Gschwendtner, MA; Haywood, D (Georgia Institute of Technology, ICC Press, 2010)
Through its involvement in the analysis, design and development of both Stirling engines and refrigerating applications, the Stirling Cycle Research Group at the University of Canterbury has, over several years, encountered a number of aspects of the practical realisation of the Stirling cycle – and indeed some aspects of its ideal realisation – which are, in our view, easily overlooked or misinterpreted. Being unaware of these aspects may possibly lead to less-than-optimal design of Stirling machines and/or misinterpretation of modelling predictions and the performance data from actual machines. The points of intended clarification are: • The misleading, or at best easily misinterpreted, typical textbook representations of the ideal Stirling cycle in both p-v and T-s property diagrams; • The difference between direct and reversed implementations of the Stirling cycle in terms of the role which the regenerator plays; • A Carnot alternative to the regenerator: The regenerator is a device that ‘conditions’ the working gas locally and not ‘globally’ as would happen in a Carnot machine. • Another difference between direct and reversed implementations of the Stirling cycle in terms of approaching the ideally isothermal heat transfer processes
Keywords: Pulse tube analysis and experimental measurements; Stirling cycle; Regenerators; Pressure; Temperature; Volume; Entropy